Pengaruh Profitabilitas, Solvabilitas, dan Umur Perusahaan terhadap Audit Delay dengan Ukuran Perusahaan sebagai Pemoderasi - Al-azhary, Intania Putri; M Karya Satya Azhar; Liza Novietta (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to determine the effect of profitability, solvency, and company age on audit delay with company size as moderation in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period with purposive sampling technique so that a research sample of 26 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period was obtained. This type of research uses associative research with a quantitative approach and uses secondary data. The data analysis technique uses multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that profitability has a negative effect on audit delay, while solvency and company age have no effect on audit delay. The MRA test results show that company size is unable to moderate the effect of profitability, solvency, and company age on audit delay.